Association of Post-Partum Depression (PPD) with Anaemia and Vitamin D Deficiency (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Postpartum depression (PPD) affects about 15% of mothers. It is a serious disorder that may affect physical and mental health of new mothers and newborns. Mothers suffering from anemia and vitamin D deficiency may be at increased risk of developing PPD.Aim: Our study aimed to detect the association of anaemia and Vit D deficiency with postpartum depression & also to look at association of other maternal and perinatal complications.Materials & methods: In this cross sectional observational study, pregnant women having anemia (Hb%